2015
DOI: 10.1111/eth.12393
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Landmarks on Territorial Behavior in a Convict Cichlid, Amatitlania siquia

Abstract: Defense of a territory is a primary factor determining the fitness of territorial individuals. Thus, territorial animals use a variety of means to lower the cost of territorial defense. Although landmarks are known to lower the defense costs of territories, little is known about how they could affect fundamental properties of territories, which could ultimately affect the demography, population regulation, individual behavior, and spatial ecology of a territorial species. This field study examined the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Increasing aquatic vegetation can increase (Barreto et al, 2011;Bhat et al, 2015;Suriyampola and Eason, 2015) or reduce (Danley, 2011) aggression. In general it should reduce visual contact among conspecifics and thus social interactions (Basquill and Grant, 1998), unless it increases fish density (Kaspersson et al, 2010).…”
Section: Aquatic Vegetationmentioning
confidence: 99%
“…Increasing aquatic vegetation can increase (Barreto et al, 2011;Bhat et al, 2015;Suriyampola and Eason, 2015) or reduce (Danley, 2011) aggression. In general it should reduce visual contact among conspecifics and thus social interactions (Basquill and Grant, 1998), unless it increases fish density (Kaspersson et al, 2010).…”
Section: Aquatic Vegetationmentioning
confidence: 99%
“…In particular, experiments on fish have been generally designed to observe preferences for particular environmental features or landmarks during a relatively short experimental time (few seconds [15], 5 minutes [16], 10 minutes [17], up to 30 minutes per trial [18]). These studies have shown for example that landmarks in a bare tank arouse interest and attract the fish [18,19] and that variations of the shape of these landmarks can change territory features [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have disagreed on the impact of a complex physical environment on aggression. Some have found that increased vegetation is associated with increased aggression [ 22 , 45 ], perhaps because the vegetation provides simple landmarks that help some individuals to monopolize an area [ 46 , 47 ]. Others have found decreased aggression in complex, vegetated, habitats [ 19 , 48 ], perhaps because these studies have measured aggression after allowing dominance-subordinate relationships to stabilize [ 49 , 50 ] or because of differences in perceived predation risk [ 51 ].…”
Section: Discussionmentioning
confidence: 99%